Perlakuan akuntansi pada budidaya udang vaname di kwanyar-bangkalan - Alfarizi, Ramadhan; Putra, Rediyanto (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the process of preparing financial statements that were applied by the vannamei shrimp farming business in Kwanyar-Bangkalan and in accordance with the financial statements with SAK EMKM. This research is qualitative research using primary data collected through direct interviews. The samples in this study were 3 vaname shrimp business actors in Kwanyar-Bangkalan. The results of the study showed that only one of the three vaname shrimp farming business actors in Kwanyar-Bangkalan who recorded financial statements in accordance with SAK EMKM